Safety vs credibility: West Papua Media and the challenge of protecting sources in dangerous places - Kayt Davies (Asia Pacific Network, 2012)
West Papua Media (WPM) is an innovative media outlet established in 2007 in response to the ongoing human rights crisis in the Indonesian provinces that self-identify as West Papua. The context of its establishment included rising hope about the potential of citizen media to empower repressed publics, complaints from mainstream media about the difficulty of establishing the credibility of reports emerging from the provinces, a ban on foreign media, and political moves by Australia to prioritise its relationship with the Indonesian government over demanding an end to oppressive military behaviour in West Papua. This article documents the strategies WPM has pioneered to bolster its credibility and protect its journalists and sources who work and live in an oppressive context. It also contextualises these strategies in relation to standard journalism processes (Lamble, 2004, 2011); current best practice about the protection of journalists in conflict zones (Cramer, 2009); and emerging concepts of global journalism ethics (Ward, 2010).